Stock market and sustainable economic growth in Nigeria - Erasmus L. Owusu (Economies, 2016)
This paper examines the relationship between stock market evolution and sustainable economic growth in Nigeria. The study employs Auto-Regressive Distributed Lag (ARDL)-bounds testing approach and a combined stock market indicators index to examine the relationship. The paper finds that, in the long run, stock markets have no positive and at best mixed effect on economic growth in Nigeria. This finding supports the numerous past studies, which have reported negative/mixed or inconclusive results on the effects of stock markets on economic growth. The paper, therefore, concludes that, there is the need for increasing financial deepening and the removal of bottlenecks in the financial sectors of the economy by providing further public and institutional education on the value of stock markets for economic development.
Keywords: C32; G15; O16; O47; 330; economic growth; stock market developments; ARDL-bounds testing approach; Nigeria